Pengaruh self efficacy, persepsi profesi guru dan lingkungan keluarga terhadap minat menjadi guru akuntansi pada mahasiswa S1 pendidikan akuntansi UNESA - Devy Ayu Prastiani; Agung Listiadi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
The research conducted has the title Influence of Self Efficacy, Perception of Teacher Profession And Family Environment On Interest in Becoming An Accounting Teacher In Undergraduate Students of Accounting Education UNESA aims to know if there is an influence between self efficacy, perception of teacher profession and environment in the family for interest in accounting teachers. Accounting Education Students faculty of Economics and Business Surabaya State University is made as a population with a total of 317 students. Where the sample was selected as many as 177 students. The method chosen for sample collection in this research is proportional random sampling technique. Data collection method in the form of questionnaires distributed to accounting education students. Researchers used multiple linear regression analysis as the analysis method for this study. From the research obtained results simultaneously the presence of positive and significant influences between self efficacy, perception of the teacher's profession and the family environment to the interest of becoming a teacher.